MORPHOMETRIC CHARACTERISTICS OF THE MAIN STRUCTURAL COMPONENTS OF THE POSTERIOR EYE WALL IN RATS UNDER THE IMPACT OF A COMPLEX OF MONOSODIUM GLUTAMATE, SODIUM NITRITE AND PONCEAU 4R - Yeroshenko, G.A.; Shevchenko, K.V.; Synenko, V.A.; Grygorenko, A.S.; Kononenko, S.V.; Zviaholska, I.M.; Onipko, V.V. (World of Medicine and Biology, 2025)
The paper presents the results of a morphometric study of the components of the posterior wall of the rat eye under the complex effect of food additives. It has been established that the endogenous effect of the complex of sodium glutamate, sodium nitrite and Ponceau-4R causes significant morphometric changes in the structures of the retina, which proves their neurotoxic properties on retinal cells and is expressed by a progressive decrease in morphometric parameters in the chronological aspect. These changes indicate the development of degenerative changes that can affect visual functions, causing their deterioration and confirm the need to limit the consumption of food additives to reduce the risks associated with visual impairment.